Economic Value Added in Managerial Economics - Rylková, Žaneta (Univerzita Pardubice, 2016)
Whether a company creates value for shareholders that is one of criteria for business performance evaluating. The paper evaluates the performance of a chosen business sector on the basis of actual business success identification in the area of enterprise value creation. The aim of this paper is to analyse and to evaluate unnamed company which operates in section CZ-NACE 25 (Manufacture of fabricated metal products, except machinery and equipment) based on the calculated values of economic value added (EVA) and to compare the results of the company with those results achieved in the whole CZ-NACE 25 sector. EVA indicator has high explanatory power since it includes the size and internal structure of invested capital, return on invested capital and the overall effect achieved by the use of capital. In order to not to transform accounting data on the economic model it has been used EVA formula based on the narrow value range calculation. The goal of the paper is to analyse and to evaluate the return on equity and the cost of equity used in the calculation of the EVA-Equity indicator both the company and the section CZ-NACE 25.
Keywords: Business performance; EVA; EVA-Equity; Business sector; Measurement; M21; L61; G32